Efficiency of Money Management and Control in the State General Authority on Minors and Similar Persons’ Funds: An Analytical Study - ALSHAHRANI, SAUD AYED; SARHAN, ALI MUFREH (Journal of Economic, Administrative and Legal Sciences, 2020)
There is no doubt that the guardianship of the funds of orphans, minors and the like is of the utmost importance, which the Kingdom of Saudi Arabia has given keen attention in all respects and has established for this purpose the State General Authority on the funds of minors and the like. And the extent to which it can carry out the objectives for which it was established. Where the purely objectives were, to identify ways to manage these funds. Evaluate the management of these funds and their ability to achieve the purpose of the street, which governs the details and mechanisms of the Authority’s work. As well as to identify the role of the supervisory bodies in the maintenance of funds that fall within the competence of the General Authority of the State. The researcher used the analytical research methodology, which was limited to studying the theoretical framework for dealing with the funds of orphans, minors and the like in light of the executive regulations of the Authority. Also, the supervisory principles governing the guarantee and safe keeping and development of such funds. The study concluded that the answer to the research questions was that there is a good management of funds that fall under the mandate of the Commission to ensure their preservation? In addition, what is the role of the financial control bodies stipulated in the Authority’s system in preserving these funds and ensuring their safety? In response to the first question, the study finds that the Authority, despite the efforts it is doing, is skeptical in its work, but may be tainted by some shortcomings, represented by some observations on the executive bylaw. Most importantly, the list did not address the termination of the mandate, which emerged as one of the main stages in the legal framework and control. In response to the second question, the Commission did not clarify the mechanisms of control over those funds. The study came up with a number of recommendations, most notably the addition of an article in the executive regulations stating the mechanism of refunding the beneficiaries in case of termination.